The Dominant Speech Functions in Cigarette Billboard Texts - Batubara, Muhammad Hasyimsyah; Nasution, Dina Syarifah (Journal of English Language Teaching and Linguistics, 2020)
This research related to speech functions in cigarette billboard texts. The objectives are to describe the category and to derive dominantly used and explain the factors of the phenomenon of speech functions. The research method used descriptive qualitative. Data was collected by applying documentary techniques from commercial cigarette billboard texts (headline, subhead, slogan and images) in public places around the city center of Medan. The finding describes of the four speech functions available only three are used in commercial cigarette billboard text, statement constitutes 18 (69.25 %), question 1 (3. 8 %), command 7 (26. 9%), and offer 0 from 26 billboard texts. Statement genre used as the dominant one because it is suitable with the pattern of commercial billboard texts, where the viewer assumed only briefly saw the display of images and written text of the billboard with a duration of 5-7 seconds when they were driving. Thus, simple and powerful information in speech function of functional grammar and the language used must be efficient, effective and able to hypnotize readers so that results in positive action on the item being advertised.